EVALUASI SISTEM MANAJEMEN MUTU INTERNAL DALAM LINGKUP PELAYANAN AKADEMIK DI UNIVERSITAS LAMPUNG - Dwi Ika Febriani (Universitas Negeri Jakarta, 2012)
This research aims to determines compatibility of (1) quality planning, (2) quality improvement, (3) quality control, and (4) quality assurance at quality assurance program of higher education in University of Lampung. Evaluation approach used in this research is objective – oriented evaluation model, with qualitative evaluation method. This research is focus on congruence between the objective of the program and its actual outcomes. Evaluation results showed that implementation of quality assurance in University of Lampung has been implemented since 2001 till now has been running well. They implemented they own concept called Unilaway. But there are some problems must be resolved, so the implementation of quality assurance in University of Lampung would be better so that the purpose of the implementation quality assurance in University of Lampung immedietaly reached.